2011
DOI: 10.1111/j.1471-0528.2011.03062.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic choriocarcinoma presenting and treated during viable pregnancy: a case report

Abstract: We present a 25-year-old Caucasian woman in her first pregnancy (conceived on clomiphene) who had an uncomplicated course until 19 weeks of pregnancy. She has given written permission for the case to be reported. Booking blood tests in 2003 showed her to be blood group A positive and negative for hepatitis B virus and HIV. A nuchal translucency scan was low risk and confirmed the gestational age. She had a past history of ileo-caecal resection for Crohn's disease 4 years earlier.Between 19 and 23 weeks of gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Although initial treatment was accompanied with β-hCG level reduction patients passed away in less than 2 years of initial treatment in Ragam et al [ 13 ] and Pezzuto et al [ 14 ] subjects. However, Bircher et al [ 15 ] case was alive and could gave birth to another child 7 years later of termination of treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial treatment was accompanied with β-hCG level reduction patients passed away in less than 2 years of initial treatment in Ragam et al [ 13 ] and Pezzuto et al [ 14 ] subjects. However, Bircher et al [ 15 ] case was alive and could gave birth to another child 7 years later of termination of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…EMA/CO: etoposide, methotrexate and dactinomycin alternating with cyclophosphamide and vincristine. First author of the study age gender presentation IBD type Tumor location Metastatic sites IHC study positive for Treatment Ragam et al [ 13 ] 46 male fever and bloody diarrhea UC Rectosigmod Liver and Kidney βhCG, CK 7, p63, CD10, and CD30 Chemotherapy with bleomycin, etoposide and cisplatin Pezzuto et al [ 14 ] 47 male abdominal pain and melena Crohn’s disease Cecum Lung and Brain β-hCG CK-pool, CK-19 and Vimentin Total colectomy with lymph-nodes dissection Bircher et al [ 15 ] 25 Female Abdominal pain and vaginal bleeding Crohn’s disease Not found Lung Not performed Chemothera py started with methotrexate and folinic acid and continued with EMA/CO …”
Section: Discussionmentioning
confidence: 99%
“…There are no recommendations on hCG concentration monitoring to diagnose choriocarcinoma on live pregnancy [3]. The disease is in question if there is abnormal vaginal bleeding and/or bleeding at metastatic sites, together with respiratory symptoms, neural/spinal signs, high beta-hCG concentration in blood, low serum HPL and snow storm image in placental sonography [6,[8][9]. Genetic and histopathologic testing will help to determine the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is the 18th reported case of antepartum choriocarcinoma resulting in both maternal and neonatal survival [2,3,4,5,6,7,10,11]. Primary pulmonary choriocarcinoma is extremely rare and associated with an overall poor prognosis [14].…”
Section: Resultsmentioning
confidence: 99%
“…In a review of the literature in 1999, Steigrad et al [2] identified 36 reported cases of choriocarcinoma with intrauterine pregnancy. Subsequently, 8 additional cases have been reported [3,4,5,6,7,8,9,10]. In addition, 1 case of tubal choriocarcinoma with concurrent intrauterine pregnancy has been reported [11].…”
Section: Introductionmentioning
confidence: 99%